The use of the skylight polarization gradient in young sandhopper’s orientation - A. Ugolini; Y. Yamahama; T. Hariyama; L. Mercatelli (Scientific Reports)
Abstract Talitrus saltator is known for its capacity to use celestial orienting cues (sun, moon, skylight spectra, and radiance gradients) to return to the damp belt of sand. adult individuals perceive radiance and/or color gradients more effectively when exposed to polarized light. expert (collected in the field) or inexpert (born in the laboratory) young of this species exhibit zonal recovery using a solar or lunar compass. Our experiments aimed to test the use of skylight polarization gradient in the zonal orientation of expert or inexpert young sandhoppers. Our observations of the rhabdom revealed that 14-day-old sandhoppers have thick and disordered microvilliThe microvillar arrangement becomes thinner and regular above 27-day-old sandhoppers it is known that the microvilli of the rhabdom in the ommatidia are involved in polarized light reception, this suggests that T. saltator perceives polarized light efficiently from approximately one month of age. Sandhoppers of various ages were tested in a transparent Plexiglas bowl under an opaline Plexiglas dome. The bowl was covered by a blue gelatin filter with a grey filter and a linear polarizing filter positioned under the blue one in such a way as to occupy half of the upper surface of the Plexiglas bowl to create a linear polarization gradient. Results show that adult and expert young sandhoppers above a month old use the linear polarization gradient, whilst inexpert young are unable to take any direction independently from their ages. Therefore, our results suggest that the use of the polarization gradient as an orientation factor needs learning in the field.